Manajemen Fisioterapi Pada Atlet Dengan Osgood-Schlatter’s Disease – Sebuah Studi Kasus - Salsabila Salsabila; Agus Widodo; Monalisa Meidania (Bali Health Published Journal, 2023)
Background: Osgood-Schlatter (OSD) Including the most common injuries that occur during productive age, this  condition occurs due to inflammation of the patellar tendon insertion at the tuberosity of the tibia. Osgood Schlatter usually occurs in children and adolescents who are active in sports, usually occurs in male adolescents aged 13-14 years and female adolescents aged 10-11 years. Purpose: Reducing pain in the right knee, reducing edema, maintaining muscle strength and increasing muscle mass M.Quadriceps, M.Hamstrings, M.Gastrocnemius, M.Gluteus, M.Adductor hip, M.Pectineus, M.Adductor longus, M. Adductor brevis, M. Adductor magnus, M. Gracilis. evaluated with 8 items sport scale. Methods: This study involved boys aged 12 years who experienced Osgood-schlatter. The exercise program was carried out for 3 weeks. Results: In this study, patients were followed up every week. The patient underwent physiotherapy sessions for 3 weeks. Patients are given measurements for muscle strength, increase in LGS, changes in segment circumference, and are obtained from the patient's ADL. Conclusion: In this study it can be concluded that after being given intervention for 3 weeks there were still no changes in Pain Level, Muscle Strength Level, Range of Joint Motion, Segment Circumference and Activity Daily Living in patients with the Osgood- Schalatter condition.